A balkáni politikai tér sajátos vonásai - Csüllög Gábor (2019)
The Balkan, as a space, has firmly kept its historical function. The Balkan has been a key area in Europe where specific cultures had come to existence and had often been controlled by powerful empires. For centuries, it had been a buffer zone between Europe and the Ottoman empire, which was, for the most part, an Asian state. Ethnic clashes started at the beginning of the 19th century simultaneously with efforts made to create an independent state. The spatiality of ethnic identities formed at different periods of history had often changed, therefore, Balkan states formed in the 19th and 20th centuries had diverse ethnic groups and religions. As a result, significant ethnic buffer spaces had come into being. During the 20the century, the Balkan states fought against one another more frequently than the powerful empires of Europe. History teaches that intertwined mosaic historical spaces cannot be “simplified” and split up permanently by political boundaries. New conflicts were created by less successful interventions of 20th century power politics. Up to the present time, even the European Union has failed to resolve the Balkan conflicts. In this study, I will analyze, from a political and geographical point of view, significant historical features of the political space of the Balkan and as well as its present state. My primary aim is to define possible dominant directions in the political spatial processes in the near future.